Experiments and kinetics of solar PCO for indoor air purification in PCO/TW system. (April 2017) - Yu, Bendong; He, Wei; Li, Niansi; Zhou, Fan; Shen, Zhihe; Chen, Hongbing; Xu, Gang
Abstract: Solar photocatalytic degradation indoor formaldehyde is an advanced technology due to its durability, stability, friendly cost and zero energy input. This article proposes a combined system of photocatalytic oxidation and Trombe wall (PCO/TW), which can simultaneously realize the space heating and removal of indoor contaminants. Ceramic fiber paper-TiO2 film was prepared by the method of dipping. Depending on the complicated working conditions of the PCO/TW system, the effects of multiple factors including formaldehyde concentration, humidity, temperature and light intensity on PCO rate should be considered. The conversion experiments under multiple factors were conducted to investigate the performance and kinetics of ceramic fiber paper-TiO2 film for photocatalytic degradation of indoor formaldehyde. The experimental factors included the typical indoor formaldehyde concentration (170–900 ppb), humidity (20%–90% RH), typical solar UV light intensity (0.21, 0.45, 0.66 and 0.90 mW/cm 2 ) and temperatures (15, 25 and 45 °C). Kinetic model simultaneously considering four explored factors was proposed. Results showed the proposed kinetic model fit the experimental data very well from the degree of fitting R 2 of 0.9711 and RMSD of 7.24%. Based on this four-variable kinetic model, factors optimizing for the target of increasing photocatalytic reaction rate in cold and warm seasons was analyzed and relative effective optimized measures were proposed. Highlights: PCO/TW system simultaneously realized space heating and air purification was proposed. Four-variable kinetic model was proposed. Effective optimized measures based on four-variable kinetic model were proposed. PCO/TW had the great potential for indoor air purification.